2020
DOI: 10.1101/2020.04.03.023861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

TMEM70 forms oligomeric scaffolds within mitochondrial cristae promotingin situassembly of mammalian ATP synthase proton channel

Abstract: Mitochondrial ATP-synthesis is catalyzed by a F1Fo-ATP synthase, an enzyme of dual genetic origin enriched at the edge of cristae where it plays a key role in their structure/stability. The enzyme’s biogenesis remains poorly understood, both from a mechanistic and a compartmentalization point of view. The present study provides novel molecular insights into this process through investigations on a human protein called TMEM70 with an unclear role in the assembly of ATP synthase. A recent study has revealed the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…In addition, TMEM70 and TMEM242 interact selectively with the c-subunit from among the 18 types of subunits present in the ATP synthase, both of them forming high molecular mass complexes with the c-subunit in the range of 60 to 150 kDa. TMEM70 was also observed in much larger complexes that may either relate to the oligomeric scaffold proposed to aid c 8 -ring assembly (27,28) or, given the tendency of the c-subunit to aggregate in vitro, they could similarly be nonphysiological experimental artifacts. In contrast to TMEM70, TMEM242 has a wider influence as the levels of subunits ATP6, ATP8, j, and k in the vestigial complexes are diminished further in its absence, similar to the effect of removing subunit c (4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TMEM70 and TMEM242 interact selectively with the c-subunit from among the 18 types of subunits present in the ATP synthase, both of them forming high molecular mass complexes with the c-subunit in the range of 60 to 150 kDa. TMEM70 was also observed in much larger complexes that may either relate to the oligomeric scaffold proposed to aid c 8 -ring assembly (27,28) or, given the tendency of the c-subunit to aggregate in vitro, they could similarly be nonphysiological experimental artifacts. In contrast to TMEM70, TMEM242 has a wider influence as the levels of subunits ATP6, ATP8, j, and k in the vestigial complexes are diminished further in its absence, similar to the effect of removing subunit c (4).…”
Section: Discussionmentioning
confidence: 99%
“…The biosynthesis of the eukaryotic ATP synthase is a highly organized process that requires the action of specific assembly factors [56,[75][76][77][78][79]. It was shown that mutations in some of these "chaperone" proteins, named ATPA12 and transmembrane protein 70 (TMEM70), can be responsible for secondary ATP synthase deficiencies [80], leading to altered assembly and compromised activity of the enzyme.…”
Section: Nuclear Gene Mutations Of Atp Synthase and Its Assembly Factorsmentioning
confidence: 99%
“…The other important regulatory protein in ATP synthase assembly is TMEM70, localized in the inner mitochondrial membrane [77]. Different mutations have been found over the years for TMEM70, with a broad spectrum of phenotypes and severity.…”
Section: Nuclear Gene Mutations Of Atp Synthase and Its Assembly Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several TMEMs in the mitochondria, including two well-studied TMEMs; TMEM70 and TMEM242. TMEM 70 is localized in the inner membrane of the mitochondria and functions as a facilitator of mammalian F1Fo ATP synthase [ 14 , 15 , 16 ]. Given the known role of TMEM70, mutations in TMEM70 lead to oxidative phosphorylation (OXPHOS) deficiencies linked to many mitochondrial diseases that present as neonatal mitochondrial encephalo-cardiomyopathy in humans [ 14 , 15 , 17 , 18 , 19 ].…”
Section: The Structure and Function Of Transmembrane Proteinsmentioning
confidence: 99%